Initial photo-degradation of PCDTBT:PC70BM solar cells studied under various illumination conditions: Role of the hole transport layer. (1st May 2019) - Züfle, Simon; Hansson, Rickard; Katz, Eugene A.; Moons, Ellen
Highlights: Initial Voc drop of encapsulated PCDTBT:PC70 BM solar cells with PEDOT:PSS HTL. Replacing PEDOTS:PSS by MoO3 as HTL prevents this burn-in degradation. Photo-degradation during first sun-hour, independent of sunlight concentration. Decay of performance with exposure dose independent of sunlight concentration. Concentrated sunlight can be used for accelerated stability assessment of devices. Abstract: Encapsulated organic solar cells often show a burn-in behaviour under illumination. This burn-in manifests itself as a rapid performance loss followed by a much slower progression of the degradation. Here we investigate the burn-in for PCDTBT:PC70 BM solar cells under a wide range of illumination intensities. We find that increasing the sunlight concentration from 1 Sun to up to 100 Suns does not change the degradation behaviour, i.e. the dependence of all principal photovoltaic parameters on the dose of solar exposure (in Sun hours). This suggests that the degradation mechanisms under solar concentration (≤100 Suns) are the same as those observed under 1 Sun. This result makes it possible to use concentrated sunlight for accelerated stability assessment of these devices. We also find that devices with PEDOT:PSS as hole transport material show a rapid drop in open-circuit voltage of around 100 mV during the first Sun hour of light exposure. By replacing PEDOT:PSS with MoO3 this initial process can be prevented and only the much slower part of the photo-degradation takes place.